Global Challenges for the Transition to «A Cashless Economy» - Zahid Farrukh Mamedov (Informaciâ i Innovacii)
The negative impact of a significant amount of cash in the national monetary system creates threats to the stability of the banking system and the economic security of the state and leads to an increase in the potential of the shadow economy. The level of development of non-cash payments and preferences in the use of non-cash payment instruments are determined by several factors: the level of economic development of the state, achievements of information and communication technologies, historical traditions and mentality of the population, as well as legislative regulation. The paper analyzes the development trends of non-cash payment systems in the developed countries of the world and the position of Azerbaijan towards the non-cash payments. The analysis of studying the system of non-cash payments in Azerbaijan, assessing the change in the share of non-cash payments are presented in the paper. The features of the policy to reduce cash payments in the Azerbaijani economy are outlined. A review of scientific literature and normative legal acts, synthesis and analysis of the information received as well as comparisons and analogies are made.